When social media feeds classic punitivism on media: The coverage of the glorification of terrorism on XXI - Aguerri, Jesús C. (Criminology & criminal justice, 2025)
This article addresses the impact of social media on media coverage of criminal justice. We specifically analyse the Spanish media coverage of the glorification of terrorism between 2011 and 2020. Via the construction of correlation networks between words, we identify key discursive elements related to this crime and its variations across time in a database of 1403 news pieces published in the digital versions of Spain’s two major newspapers, ABC and El País. The analyses show how the media have focused their interest on the relationship between social media and the dissemination of certain offensive and/or criminal content while ignoring the element of ‘terrorism’. We discuss how the appearance of such offences in social media and the reaction of the Criminal Justice System are turned into object of mediatic interest, while many of the traditional communicative keys regarding the coverage of both the crimes and the penal system remain untouched.